Hubungan Kesejahteraan Psikologis dengan Kontrol Diri pada Remaja di Bukittinggi - Dilla Karmila; Rida Yanna Primanita (Lembaga Pengembangan Kinerja Dosen, 2025)
Individuals can exercise self-control if they feel psychologically well. If self-control is low, psychological well-being is also low. Researchers want to see if there is a significant relationship between psychological wellbeing and self-control in Bukittinggi adolescents. The research approach used is a quantitative approach with a correlational method. The population in this study were adolescents in Bukittinggi while the sample in this study were several adolescents in Bukitinggi. Sampling in this study used a sampling technique, namely non-probability sampling and this study used the technique of distributing questionnaires or questionnaires distributed online. The number of samples obtained in this study were 117 people. The results show that there is a significant positive relationship between psychological well-being and self-control in adolescents in Bukittinggi City. One of the things that affects self-control in adolescents in Bukittinggi City is psychological well-being. Psychological well-being affects self-control by 71.2%. So that the remaining 28.8% is influenced by other factors. Based on the overall research results, there is a positive relationship between psychological well-being and self-control in adolescents in Bukittinggi City. From this study, it is also found that the relationship has a positive and linear direction so that when psychological well-being is high, self-control is also high. Conversely, if psychological well-being is low, self-control will also be low.